Changing the World Through Poetry: Confessions, Poems and Banners of Adam Borzič - Kittlová, Markéta (Porównania, 2020)
This study focuses on Adam Borzič, one of the most distinctive contemporary Czech poets. The study contextualises his work within current Czech poetry but also examines his other work that is not strictly classified as art as though it were cultural work with avant-garde features. It investigates four volumes of Borzič’s work in terms of the changes in the author’s creative gesture, which expands from his conviction that the world is at a turning point and the avant-garde longing to change the world by poetry. In the four volumes of Borzič’s poetry (written so far), this gesture is embodied through delicately intimate, acutely physical, or even gigantically all-embracing positions, where he employs motives of the heart, head, hand and mouth. The study attempts to evaluate the change in Borzič’s work in the light of T. S. Eliot’s understanding of the social role of poetry and avant-garde longing to change reality through art. The Czech poet, Adam Borzič, is one of the most distinctive figures of the current Czech literary scene. His poetry is distinct because of its unique gesture and also represents a strong current in the poetry production of the past decade with its emphasis on the social function of poetry7 and the poet’s role as somebody who should nurture the world through his/her work or even change it. This study attempts to portray Borzič’s work as focused on the mentioned topics and related issues of the end of the first decade of the twenty-first century and renew interest in them, contextualise his work within current Czech poetry but also investigate his other work, which is not strictly artistic but which possesses some avant-garde features.